Dependence of acoustic noise emission on the dissipated energy of plunging waves - Zygmunt Klusek; Maciej Paprota; Wojciech Sulisz; Aneta Zdolska; Sebastian Sorek (Oceanologia)
Summary: The results of experiments performed in a wave flume designed to explore associations between the dissipation of surface wave energy during breaking and acoustic noise emission are presented. The experiments were carried out using tap water in the wave laboratory of the Institute of Hydro-Engineering of the Polish Academy of Sciences, Gdańsk, Poland. In particular, being shown are the parameters of empirical dependency between the dissipated wave energy during plunging and the energy of pre-breaking wave trains. Relationships between wave energy losses in the case of breakers with an amplitude of about 10 cm and the noise acoustic energy in the frequency band from 80 to 12,500 Hz were estimated. Taking into consideration the phenomena of reverberations and propagation in an acoustical waveguide, a numerical model was used for the correction of the observed noise's acoustic spectra. A detailed analysis of the factors affecting the noise level in the semi-enclosed volume allowed us to specify the rate of conversion of the wave energy dissipated during breaking into acoustic energy, which was found to be in the order of 10−8. Keywords: Wave breaking, Wave energy dissipation, Underwater noise